2022
DOI: 10.3390/nano13010116
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Removal of Ciprofloxacin from Contaminated Water via Polystyrene Anion Exchange Resin with Nanoconfined Zero-Valent Iron

Abstract: Ciprofloxacin (CIP), an important emerging contaminant, has been frequently detected in water, and its efficient removal has become an issue of great concern. In this study, a nanocomposite material nZVI/PA was synthesized by impregnating nanoscale zero-valent iron (nZVI) inside a millimeter-sized porous host (polystyrene-based anion exchange resin (PA)) for CIP removal. The nZVI/PA composite was characterized by field emission scanning electron microscopy coupled with energy-dispersive X-ray, transmission ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…As an environmentally friendly and cost-effective oxidant, H 2 O 2 is also widely used as an oxidant in AOPs, since the decomposition products of H 2 O 2 are harmful H 2 O and O 2 ions [106]. The traditional Fenton process adopts ferrous salts as catalysts for the activation of H 2 O 2 , which not only requires a limited pH range (2.0-4.0), but also requires a large amount of ferrous salts, leading to the formation of massive sludge and a wastage of iron [107]. Ferrous ions generated from the slow dissolution of nZVI can promise the production of ROS (e.g., •OH, etc.)…”
Section: Hydrogen Peroxide-based Aopsmentioning
confidence: 99%
See 4 more Smart Citations
“…As an environmentally friendly and cost-effective oxidant, H 2 O 2 is also widely used as an oxidant in AOPs, since the decomposition products of H 2 O 2 are harmful H 2 O and O 2 ions [106]. The traditional Fenton process adopts ferrous salts as catalysts for the activation of H 2 O 2 , which not only requires a limited pH range (2.0-4.0), but also requires a large amount of ferrous salts, leading to the formation of massive sludge and a wastage of iron [107]. Ferrous ions generated from the slow dissolution of nZVI can promise the production of ROS (e.g., •OH, etc.)…”
Section: Hydrogen Peroxide-based Aopsmentioning
confidence: 99%
“…Furthermore, a basic solution is not only adverse to the corrosion of nZVI, but also unfavorable for the adsorption of negatively charged contaminants [140]. The removal efficiency of contaminants can also be significantly affected by inorganic anions and organic compounds (Figure 12) [107,137,138]. Furthermore, the reusability investigation indicated that the removal efficiency decreased significantly in the recycling process of nZVI materials, which may be attributed to the formation of iron oxide on nZVI, resulting from the deactivation of nZVI with DO (Figure 12) [107,139,140].…”
Section: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations